European Metrology Project for III-V Materials Based High Efficiency Multi-Junction Solar Cells. Issue 1771 (8th May 2015) - Cuenat, Alexandre; Selezneva, Ekaterina
ABSTRACT: Since July 2014, thirteen European metrology organizations are collaborating to address some of the main metrological challenges faced by the developments of high-efficiency III-V multi-junction solar cells (MJSC). III-V MJSC structures are made of a high number of layers, which makes a pure experimental optimization difficult and expensive; this also limits the uncertainty of cell calibration due to the complexity of their spectral response. The project is structured in three distinct parts: 1) improved accuracy in materials and transport characterization for existing MJSC; 2) improved accuracy and repeatability in traceable efficiency characterization for MJSC cells with three or more junctions and finally, 3) metrology for advance concept such as coupling with thermoelectric, dilute nitride, quantum dots or growth on Silicon. Each part of the project is briefly introduced and we present NPL initial results in developing accurate and spatially resolved metrology to determine traceable and complete III -V material data sets.